Penggunaan Model Problem Based Learning dalam Pembelajaran Bahasa Indonesia Pada Era Vuca - Lisnawati, Iis; Ruslan, Titin Setiartin; Kartadireja, Welly Nores (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this research is to describe the use of the Problem Based Learning model in Indonesian Language Learning in the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) era. VUCA is a condition that shows rapid, unpredictable, uncertain, complex, and unpredictable changes in various fields, especially education. In this study used the method of literature study. The data analysis techniques used were (1) Examining VUCA and its possible problems and solutions in learning Indonesian, (2) Examining various components in learning Indonesian that might be a solution to the problems encountered in learning Indonesian, (3) Determine components that have great opportunities as solutions to overcome problems in the VUCA era, namely learning models because in the use of learning models other learning components can be integrated. (4) Synchronization between the characteristics of the problems that might arise in the VUCA era, general learning principles (scientific approach), specific principles of Indonesian language learning (genre-based approaches, genre pedagogy, and Content Language Integrated Learning -CLIL), use of ICT, HR demands XXI century, character that must be built or internalized, and independent learning, and (5) Designing synchronization results in the form of material content and activities to be carried out in PBL steps. The results of the research are in the form of a PBL model design in Indonesian language learning in the VUCA era that collaborates and integrates general learning principles, Indonesian language learning principles, the demands of 21st century human resources, ICT, the character that students must have, independent learning in PBL steps to achieve learning objectives that have been set.